Implementasi Hak Perlindungan Anak di Lingkungan Pendidikan untuk Menciptakan Sekolah Aman - Rima Nuryani; Risbon Sianturi; Regita Nurul; Yuliana Putri; Fatimah Az-Zahra (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Child protection in educational settings is a crucial issue in creating safe and child-friendly schools. However, in practice, various problems such as violence, bullying, and discrimination are still experienced by students. This study aims to analyze the implementation of child protection rights in educational environments and to identify the challenges and solutions in establishing safe schools. The research method used is a literature review by examining scientific journals, international organization reports, and regulations related to child protection. The results show that although Indonesia has a strong legal framework, its implementation in practice is still not optimal. This is influenced by cultural factors, lack of educators’ understanding, and weak supervision and inter-agency coordination. Therefore, strengthening policies, improving educators’ capacity, and involving families and communities are necessary. This study recommends a more comprehensive and collaborative approach to create safe, inclusive, and child-centered educational environments